Gambaran Asupan Zat Gizi, Konsumsi Sayur dan Buah dengan Status Haemoglobin Siswa SMP - Hartati, Yuli; Telisa, Imelda; Susanto, Eddy; Siregar, Afriyana (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2021)
Background : Anemia in adolescents is one of the nutritional problems in Indonesia. The main cause is related to the intake of nutrients, especially energy and protein, as well as the consumption of vegetables and fruit. The Purpose : This study aims to determine the intake of energy, protein, and consumption of vegetables and fruit in adolescents and anemia status in adolescents. Methods : This study used a cross-sectional design, sampling was done by simple random sampling. The research location is in SMP Muhammadiyah 4 Palembang. Results : The results showed that respondents with normal hemoglobin (Hb) status, which was 61.5%, and 53.8% less nutritional knowledge. Lack of energy intake by 57.7%. A good intake of animal protein was 69.2% and a vegetable protein intake of less category was 78.8%. Good fat intake is 53.8%. Less carbohydrate intake by 55.8%. Vegetable consumption is less than the requirement of 71.2%. Consumption of fruit is less than the requirement of 63.5%. respondents with normal Hb status had good nutritional knowledge of 83.3%, a good energy intake of 63.3%, good animal protein intake of 72.2%, good vegetable protein intake of 90.9%, a low fat intake of 79, 2%, good carbohydrate intake is 78.0%, good vegetable consumption is 73.3%, good fruit intake is 73%. Respondents with less energy and protein intake tend to experience anemia. Conclusion : Adolescents with less consumption of vegetables and fruit tend to have the anemic status